2019
DOI: 10.1109/access.2019.2915533
|View full text |Cite
|
Sign up to set email alerts
|

Driving Fatigue Classification Based on Fusion Entropy Analysis Combining EOG and EEG

Abstract: The rising number of traffic accidents has become a major issue in our daily life, which has attracted the concern of society and governments. To deal with this issue, in our previous study, we have designed a real-time driving fatigue detection system using power spectrum density and sample entropy. By using the wireless technology and dry electrodes for EEG collection, we further integrated virtual reality simulated driving environment, which made our study more applicable to realistic settings. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 66 publications
(55 reference statements)
0
28
0
Order By: Relevance
“…The study [28] applied the multiscale entropy (MSE) to evaluate fatigue in a SSVEP-BCI task and achieved an accuracy rate up to 97%. In [32], multiple entropy calculation methods combined EEG and EOG were applied to the driving fatigue classification, resulting an average accuracy rate round 99%, [33] combined multiple EEG channels and various entropy calculation together, hit the highest accuracy of 97.5% for driving fatigue detection. Those methodologies can provide good classification performance.…”
Section: Introductionmentioning
confidence: 99%
“…The study [28] applied the multiscale entropy (MSE) to evaluate fatigue in a SSVEP-BCI task and achieved an accuracy rate up to 97%. In [32], multiple entropy calculation methods combined EEG and EOG were applied to the driving fatigue classification, resulting an average accuracy rate round 99%, [33] combined multiple EEG channels and various entropy calculation together, hit the highest accuracy of 97.5% for driving fatigue detection. Those methodologies can provide good classification performance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, to measure the complexity of EEG time series, Wang et al proposed a fusion entropy (sample entropy, approximate entropy, and spectral entropy) analysis method for EEG and EOG signals. Results showed that the average accuracy of the fusion entropy analysis method combined with EOG and EEG can reach 99.1±1.2% [43]. Furthermore, Zhu et al discussed the performance of multi-user MI-BCI idle detection based on common spatial pattern (CSP) and brain network features and proposed several cross-training feature fusion strategies [31].…”
Section: B Feature Fusion Strategymentioning
confidence: 99%
“…The internal complexity of a lithium-ion battery varies with the degradation of the battery; thus, the SampEn of the voltage sequence could be an effective signature correlated to battery health. At present, SampEn has been applied in the analysis of wind-power generation, heat-exchange performance, heart-rate variability, and time series of diagnostic cases [43]- [45].…”
Section: ) Sample Entropy (Sampen))mentioning
confidence: 99%